Serum afamin and its implications in adult growth hormone deficiency: a prospective GH-withdrawal study - Ratku, Balázs; Lőrincz, Hajnalka; Csiha, Sára; Sebestyén, Veronika; Berta, Eszter; Bodor, Miklós; Nagy, Endre V.; Szabó, Zoltán; Harangi, Mariann; Somodi, Sándor (Frontiers in Endocrinology, 2024)
Introduction: Adult growth hormone deficiency (AGHD) is associated with a high prevalence of metabolic syndrome (MS), which contributes to the unfavorable cardiovascular risk profile in these patients. Insulin like growth factor-1 (IGF-1) is a widely used biomarker, however it does not always reflect the cardiometabolic risk and has a poor relationship with clinical efficacy endpoints. Consequently, there is an unmet need for biomarkers to monitor responses to GH-replacement. Afamin is a hormone-like glycoprotein, expressed in the liver. Higher afamin levels are strongly associated with MS and insulin resistance (IR). Although both MS and IR are very common in AGHD, afamin has not been investigated in these patients.To investigate afamin as a potential biomarker in patients with AGHD.Participants included 20 AGHD patients (11 GH-substituted and 9 GHunsubstituted) and 37 healthy controls. Subjects underwent routine laboratory examinations, anthropometric measurements, body composition analysis using multi-frequency bioelectrical impedance analysis (InBody720) and measurement of serum afamin concentrations. In GHsubstituted subjects, GH-substitution was withdrawn for 2 months. Measurements were carried out right before GH-withdrawal, at the end of the 2-month withdrawal period, and 1 month after reinstituting GH-replacement therapy (GHRT).Results: GH-unsubstituted patients demonstrated higher afamin levels compared to controls (p=0.03). Afamin positively correlated with skeletal muscle mass, bone mineral content, total body water, extracellular-and intracellular water content, insulin (all, p<0.01), HOMA-IR (p=0.01) and Cpeptide (p=0.03) levels in AGHD but not in healthy controls. In GH-substituted patients 2-month of GH-withdrawal caused significant changes in body composition, including decreased fat-free mass, skeletal muscle mass, total body water, and intracellular water content (all, p<0.01); but these changes almost fully recovered 1 month after reinstituting GHRT. Unexpectedly, afamin levels decreased after GH-withdrawal (p=0.03) and increased with reinstitution (p<0.01). Changes of afamin levels during GH-withdrawal positively correlated with changes of HOMA-IR (r=0.80; p<0.01) and changes of insulin (r=0.71; p=0.02).Higher afamin levels in unsubstituted AGHD patients might indicate severe metabolic dysregulation. Significant changes accompanying GH-withdrawal and reinstitution, along with strong correlations with measures of IR , suggest that afamin could be a promising biomarker to monitor GHRT-associated changes of insulin sensitivity.